2021
DOI: 10.1007/s12325-021-01840-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Viscoelastic Substance Injection Versus Air Filling in the Anterior Chamber During Foldable Capsular Vitreous Body (FCVB) Implant Surgery: A Prospective Randomized Controlled Trial

Abstract: Introduction To compare the outcomes of viscoelastic substance injection with air filling in the anterior chamber during foldable capsular vitreous body (FCVB) implant surgery in patients with severe retinal disease. Methods Thirty eyes with severe retinal diseases were randomly divided into two groups. In the viscoelastic group, 0.15-0.2 mL of 1.7% sodium hyaluronate was injected into the anterior chamber after FCVB implantation; in the air group, the anterior chamber … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…In our study, there was a case of a shallow anterior chamber after surgery, which may have been related to the insufficient amount of viscoelastic substance injected into the anterior chamber during the operation. Although filtered clean air can also be used to fill the anterior chamber to maintain the intraocular pressure and depth of the anterior chamber, the study by Zhang et al 27 showed that viscoelastic substances are better. Valve leakage and foreign body sensation can be avoided if the valve is made smaller in the future.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, there was a case of a shallow anterior chamber after surgery, which may have been related to the insufficient amount of viscoelastic substance injected into the anterior chamber during the operation. Although filtered clean air can also be used to fill the anterior chamber to maintain the intraocular pressure and depth of the anterior chamber, the study by Zhang et al 27 showed that viscoelastic substances are better. Valve leakage and foreign body sensation can be avoided if the valve is made smaller in the future.…”
Section: Discussionmentioning
confidence: 99%
“… 10 Thus, we found that FCVB displayed better results in retinal reattachment, which is consistent with previous studies. 7 …”
Section: Discussionmentioning
confidence: 99%
“… Liu N et al 31 2021 5 SO-dependent eyes; 32.0(18–46) 3(5) 12 to 15 months Observed 5 patients of severe silicone oil-dependent eyes underwent FCVB implantation The FCVB is a safe, feasible, and effective vitreous substitute to maintain ocular morphology and intraocular pressure Xu X et al 5 2021 18 Ocular trauma; SO-dependent eyes 50.6(34–70) 17(18) 12 months Observed 18 patients who underwent vitrectomy and FCVB implantation for severe ocular trauma and silicone oil-dependent eyes FCVB implantation is an effective and safe treatment for eyes with severe ocular trauma and silicone oil-dependent eyes. Zhang Z et al 7 2021 27 RD; posterior trauma Air group:41.8±13.5 Viscoelastic group:42.4±14.2 Air group:10 (13) Viscoelastic group:11(14) 6 months To compare the outcomes of viscoelastic substance injection with air filling in the anterior chamber during FCVB implant surgery in patients with severe retinal disease. The use of viscoelastic substances in the anterior chamber during FCVB implant surgery was associated with less fluctuation in postoperative IOP and could reduce postoperative complications Abbreviations : RD, retinal detachment; CHD, choroidal detachment; SO, silicone oil.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations